The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/08995605.2020.1794478
|View full text |Cite
|
Sign up to set email alerts
|

An advanced perspective on moral challenges and their health-related outcomes through an integration of the moral distress and moral injury theories

Abstract: Both the models of moral distress and of moral injury place an emphasis on various types of moral challenges that may violate the individual’s conscience, evoking moral emotions. Yet, there appears to be great conceptual confusion as regards both scholarly perspectives. The purpose of this article is to further elaborate on the qualitative content and conceptual demarcations of the theories of moral injury and moral distress. In the light of this theoretical elaboration, we propose an integrated moral distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Although the concepts of MD and MI share similarities, there remains ambiguity around their definitions ( 15 , 27 , 28 ). One approach proposed by Litz and Kerig ( 29 ) is to conceptualize MD and MI as existing on a continuum, with MD appearing on the less severe end of this spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concepts of MD and MI share similarities, there remains ambiguity around their definitions ( 15 , 27 , 28 ). One approach proposed by Litz and Kerig ( 29 ) is to conceptualize MD and MI as existing on a continuum, with MD appearing on the less severe end of this spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have suggested that MD and MI result from different types of insults, with MD resulting from the long-term accumulation of damage from organizational oppression, while MI results from the immediate harm resulting from a single substantial act going against individual beliefs ( 30 ). Given the limitations of these definitions, it has been suggested to integrate and synthesize the concepts of MD and MI as one, to better explore moral stressors holistically ( 28 ). Accordingly, we have taken a similar approach to explore these concepts conjointly in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The curriculum focuses on the learning objective of de ning and normalizing emotional and moral distress during global health work and developing a resiliency strategy for staying well while working outside of the US (24). One key aspect is creating a space for students to re ect on their personal challenges with developing resiliency.…”
Section: Resiliency and Wellnessmentioning
confidence: 99%
“…After military service, former military personnel may develop post-traumatic stress disorder (PTSD) or other related psychiatric conditions, which may impair their adaptation to a new post-military, civilian life (Grimell, 2018a, p. 193). These challenges involve physical, mental and moral elements (Shay, 1994;Grimell, 2018b;Molendijk, 2018;Grimell and Nilsson, 2020;p. 380).…”
Section: Introductionmentioning
confidence: 99%
“…After military service, former military personnel may develop post-traumatic stress disorder (PTSD) or other related psychiatric conditions, which may impair their adaptation to a new post-military, civilian life ( Grimell, 2018a , p. 193). These challenges involve physical, mental and moral elements ( Shay, 1994 ; Grimell, 2018b ; Molendijk, 2018 ; Grimell and Nilsson, 2020 ; p. 380). A study on United States combat veterans vs. non-combat veterans revealed that combat veterans are more than three times as likely to screen positive for lifetime PTSD ( Thomas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%